Predictive validity of the AUDIT for hazardous alcohol consumption in recently released prisoners - Thomas, E.; Degenhardt, L.; Alati, Rosa; Kinner, S. (Elsevier Ireland Ltd, 2014)
Background: This study aimed to assess the predictive validity of the Alcohol Use Disorders Identification Test (AUDIT) among adult prisoners with respect to hazardous drinking following release, and identify predictors of post-release hazardous drinking among prisoners screening positive for risk of alcohol-related harm on the AUDIT. Methods: Data came from a survey-based longitudinal study of 1325 sentenced adult prisoners in Queensland, Australia. Baseline interviews were conducted pre-release with follow-up at 3 and 6 months post-release. We calculated sensitivity, specificity and area under the receiver operating characteristic (AUROC) to quantify the predictive validity of the AUDIT administered at baseline with respect to post-release hazardous drinking. Other potential predictors of hazardous drinking were measured by self-report and their association with the outcome was examined using logistic regression. Results: At a cut-point of 8 or above, sensitivity of the AUDIT with respect to hazardous drinking at 3-month follow-up was 81.0% (95%CI: 77.9-84.6%) and specificity was 65.6% (95%CI: 60.6-70.3%). The AUROC was 0.78 (95%CI: 0.75-0.81), indicating moderate accuracy. Among those scoring 8 or above, high expectations to drink post-release (AOR: 2.49; 95%CI: 1.57-3.94) and past amphetamine-type stimulant (ATS) use (AOR: 1.64; 95%CI: 1.06-2.56) were significantly associated with hazardous drinking at 3 months post-release. Results were similar at 6 months. Conclusions: Among adult prisoners in our sample, pre-release AUDIT scores predicted hazardous drinking six months after release with acceptable accuracy, sensitivity and specificity. Among prisoners screening positive on the AUDIT, expectations of post-release drinking and ATS use are potential targets for intervention to reduce future hazardous drinking. © 2013 Elsevier Ireland Ltd.